Em Questão: v. 20, n. 2 (2014) - Bandeira, Pablo Matias (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número: http://www.seer.ufrgs.br/index.php/EmQuestao/issue/view/2378/showToc